2018
DOI: 10.1159/000497073
|View full text |Cite
|
Sign up to set email alerts
|

Health Literacy: The Reality of a Community in Alto Minho

Abstract: Background: Limited health literacy makes decision-making difficult and has implications for individual health, costs, and the organization of health systems in general, and therefore must be studied in different communities, allowing an adequate response to the specificities, particularities, and potentialities of each local situation. Methods: To evaluate the level of health literacy and relate it to sociodemographic variables (sex, age group, education, and employment situation), this study was carried out … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(49 citation statements)
references
References 10 publications
(23 reference statements)
0
48
0
Order By: Relevance
“…Twelve studies focused on nurses as the study population, particularly on their practices and knowledge about peripheral intravenous catheterization 12,13,15,18,22,26–30,33,35. Thirteen studies characterized the nursing teams, with high sociodemographic, academic, and professional representativeness 12–15,22,26–29,33,35–37. The sample size in the included studies ranged from 1815 to 92 nurses 14.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Twelve studies focused on nurses as the study population, particularly on their practices and knowledge about peripheral intravenous catheterization 12,13,15,18,22,26–30,33,35. Thirteen studies characterized the nursing teams, with high sociodemographic, academic, and professional representativeness 12–15,22,26–29,33,35–37. The sample size in the included studies ranged from 1815 to 92 nurses 14.…”
Section: Resultsmentioning
confidence: 99%
“…Some studies identified specific practices regarding tourniquet use during PIVC insertion 12,14,18,34,35–37. Salgueiro-Oliveira et al35 observed that nurses used elastic tourniquets or latex gloves and that tourniquets sometimes remained in nurses' uniform pockets and were used between patients without prior decontamination.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations